Genomic Determinants and Antimicrobial Resistance Pattern of Clinical Isolates of Extended Spectrum Beta Lactamase (ESBL) Producing Escherichia coli - Hamid Ahmad Shah; Arshi Syed; Mohd Altaf Bhat; Dalip K. Kakru; Shaheen Farooq; Sabia Qureshi; Azhar Shafi; Burhan Nabi; Anil Taku (Journal of Pure and Applied Microbiology, 2023)
The growing prevalence of antibiotic-resistant bacteria is a worldwide public health apprehension, and Escherichia coli (E. coli) is one of the most commonly implicated bacterial species. Among E. coli isolates, extended-spectrum β-lactamase (ESBL)-producing strains have been identified as a key contributor to antibiotic resistance. Penicillin’s, cephalosporins, and monobactams are only a few of the β-lactam antibiotics that can be rendered inactive by ESBLs. This investigation’s goals were to determine the prevalence of ESBL-producing E. coli isolates found in clinical samples and to analyze the distribution of the blaTEM, blaSHV, and blaCTX-M genes among them. Additionally, we aimed to determine the antibiotic susceptibility patterns of these isolates to other antibiotics. Clinical isolates from urine, ear swab, and wound/pus swabs were collected from patients with suspected E. coli bacterial infections from different regions of north India viz., SKIMS-JVC medical college and NABL accredited Dr. Qadri’s Lab both from Srinagar Kashmir valley region and SMSR, SU from Greater Noida UP. Standard laboratory techniques were used to identify E. coli isolates, and the combined disc method and other phenotypic confirmation techniques were used to confirm ESBL formation. PCR amplification and sequencing were used to find the blaTEM, blaSHV, and blaCTX-M genes. The Kirby-Bauer disc diffusion method was used to test the antimicrobial susceptibility of various bacteria to different antibiotics. A total of 210 E. coli isolates were collected from different clinical samples and only 158 isolates showed positive results for ESBL by DDST and phenotypic confirmatory tests. Of these, 124 (78.48%) were ESBL-producing isolates. We found that blaTEM was the most prevalent gene (45.16%), followed by blaCTX-M (34.16%) and blaSHV (12.09%). Antimicrobial resistance profiles were assessed for each of the 120 isolates. Ampicillin and Cefepime were the most resistant drugs to ESBL-producing isolates, followed by Gentamicin, Ceftriaxone, and Cefixime.